ARCHAEOLOGICAL REFLECTIONS ON ANCIENT EGYPTIAN RELIGION AND SOCIETY - Okon, Etim E. (European Scientific Journal, ESJ, 2012)
This paper examined the historical and archaeological evidences of the impact of religious beliefs on ancient Egyptian society and culture. Religion had a pervasive influence in ancient Egypt. Ancient Egypt was a theocracy with Pharaoh as the God-king. Religious exigencies guided statecraft to the extent that social and public policies were dictated by religious considerations. Ancient Egyptians trusted the efficacy of indigenous beliefs and at times displayed belligerent courage in resisting any anti-religious influence in social and political terrain. Religion was not only a social phenomenon, but also the platform for attainment of immortality. The paper employed the historical analogy and documentary method to arrive its conclusion which included the fact that archaeological research has a strong relationship in the study of the ancient religions of Egypt.